Exploratory testing for platform video games: strategies and lessons learned - Duarte, Yohan; Mandelli, Henrique Canella; Durelli, Vinicius; Nardi, Paulo Augusto; Endo, Andre Takeshi (Journal on Interactive Systems, 2024)
With the growth of the digital games market, the occurrence of bugs in games has a significant impact and generates dissatisfaction among users. Therefore, conducting tests is necessary to avoid these events and ensure the quality of the distributed product. Among the tests that are performed in games, one that is particularly effective in identifying bugs from the user's perspective is exploratory testing, but this is little covered in game testing literature, not providing new testers with guides or paths to be used for specific occasions. This paper reports an experience of applying exploratory testing strategies in 2D and 3D platform games. We selected seven well-known strategies of exploratory testing and conducted a study that involved the definition of a game testing procedure and proper adaptations for the games under test. By applying the game testing procedure, several bugs with low, medium and high severity were uncovered. The lessons learned and routines carried out in this study can be used by new testers in games of the same category, in an attempt to obtain better results.